INFRASTRUCTURE IN TRANSFORMATION, A SPATIAL STUDY ON THE VALUES OF OBSOLETE MOBILITY INFRASTRUCTURE - Jarneving, Carl (My University, 2020)
Our cities are complex systems in perpetual motion. They are the very reflection of our current and past societies. They are the physical manifestation of layers of time. Where past civilizations stood with their temples and other religious structures as embodiments of their time, we stand with our skyscrapers, airports, highways and other infrastructural elements as monuments of our age. In an ever globalizing and transitioning world, systems and its supportive structures change over time. On a path to a sustainable future, the mobility sector and notion of private ownership is likely to go through considerable transformations. Modern cities are centralized around the car, with streets, avenues and highways pulsing through the city’s most central locations. They represent a network of barriers and potentials. In a shift to a public space city, these structures would undergo transformation. Some would be considered obsolete remnants of history whereas some would be readapted for a new purpose. This thesis aims to, in a speculative manner, investigate and visualize the potential of such transformation. The research is conducted through a series of spatial experiments with both general and site specific approaches. It investi- gates what inherent value these structures might hold when gradually transformed and how they can be imagined as catalyzers for new hybrid typologies and urban synergies. The methodology used is a parametric generalized model of an infrastructure system with Gothenburg as a test site. Given the standardized nature of these systems, they are categorized into typologies and with the help of a parametric model the thesis proposes a system applicable to multiple infrastructural scenarios. The outcome is a suggestive design scenario visualizing, for a selected and representative site, how an area could use a specific selection of obsolete infrastructure elements to create a new hybrid typology: a responsive compilation of functions adding value, restoring local ecology and visualizing how deconstruction and upcycling can be used as a initiator of change.
Keywords: infrastructure, mobility, typology, hybrid, speculative, public space, catalyzer, obsolete, urbanization, transformation